Poliuretanos termoplásticos : efeito de diferentes processos de síntese nas propriedades térmicas, mecânicas e reológicas - Saft, Graziella Kassic (2017)
Thermoplastic polyurethanes (TPUs) are polymers which can be used widely in many fields, such as shoes industry and engineering parts. They can be produced by two different synthesis methods, known by one step process or two step one. These methods can influence the separation between hard and soft segments and also their morphological, rheologycal, thermal and mechanical properties. This work studied morphological, rheologycal, thermal and mechanical properties of TPUs produced by these different synthesis methods, before and after their thermal treatment (annealing). Two step process was made by batch, although one step process was made by continuous production. Annealing influenced thermal and mechanical properties, increasing cristalinity, thermal stability and mechanical performance, such as abrasion resistance, tensile strenght and tear one. Besides that, it was determined that one step process made a TPU which has lower polydispersity than TPU made by two step one. It was realized that once annealing is applied to a sample obtained by batch process, it was increased its thermal and mechanical performance.